423 Endoscopic Balloon Dilatation for Paediatric Subglottic Stenosis: Systematic Review and Meta-Analysis. (19th August 2022) - Ravikumar, N
Abstract: Aim: Subglottic stenosis (SGS) is a rare life-threatening condition that involves a narrowing of the airway. It may be congenital or acquired affecting children predominantly. Traditionally, it has been treated by surgical interventions, but in recent times a shift towards minimally invasive Endoscopic Balloon Dilatation (EBD) has been observed. This review aims to identify whether EBD is a safe approach in the treatment of SGS in the paediatric population. Method: A systematic review was performed on EBD for paediatric SGS in compliance with the PRISMA guidelines. Studies published from 2000 onwards, with sample size greater than 5 and described EBD without adjuvant procedures were included. A meta-analysis of proportions was performed using the R software. Results: 25 studies were included, with a total of 1109 patients, of which 920 underwent EBD. The mean sample size of the studies is 43.48 (range 5–166), and the grand mean age is 3.77 years (range 0.7–17 years). Primary outcome assessed was technical success. A high overall technical success rate (successful decannulation and avoidance of tracheostomy/laryngotracheal reconstruction) was observed (83.95%, 95% CI [75.08% - 89.58%]). Similarly, low levels of mortality (3.29%, 95% CI [1.14% - 9.14%]), and high rates of symptom improvement (73.65%, 95% CI [57.81% - 85.09%]) were also observed. Conclusion: EBD is a successful procedure in majority patients, with low levels of adverse events and marked symptom improvement. It is therefore a safe alternative to current procedures in the management of paediatric SGS.